Intracranial extension of parotid adenoid cystic carcinoma presenting as trigeminal neuralgia: A case report - Hassouneh, Ammar (2025)
Being rare malignancies, parotid gland adenocarcinomas are most significantly represented by the ACC subtype due to their aggressive nature and propensity for PNI. We present a case of a 56-year-old male with right-sided trigeminal neuralgia and facial palsy, diagnosed with ACC of the parotid gland with intracranial extension. Tumor progression occurred with brain, lung, and liver metastases, so he was placed on palliative care despite chemotherapy. This case underscores the diagnostic and management challenges associated with ACC with PNI.